Approaches are considered to planning of theatrical placards for différent their operating conditions - V.N. Krasheninnikov; V.I. Krivoruchkin (Academy of Cognitive and Natural Sciences, 2007)
The method of the associative planning is expounded on the example of playbill fo r raising of tragedies V. Shakespeare.